Avaliação da influência de diferentes métodos de aumento de temperatura na resistência de união de um sistema adesivo de condicionamento ácido total. - Carvalho, Marcos Paulo Marchiori (2013)
Purpose: Different methodology of adhesion have been tested in order to promote better bonding strength between dentinal substrate and composite resin. The increase of temperature associated with the solvent evaporation, it has been one of the ways of modifying the protocol in order to obtain better adhesion. Materials and Methods: For this study, were tested two different methodologies to increase adhesive temperature. The control group 1 (n=4) were tested under environmental temperature; group 2 (n=6) consisting of heating the adhesive in an experimental apparel before the adhesive to be applied and the group 3 (n=6) consisting in increasing of the temperature of the adhesive by application of warm air steam over adhesive applied on dentin. It was applied the tukey test at 5% probability. Results: The results of the study showed no statistically significant difference in comparison with the groups. (G1: 48,52ª, G2: 40,35ª, G3:47,21ª) Conclusion: This study concludes that the increase of temperature did not cause significant differences on bond strength.